Agresivitas Pajak Terhadap Agresivitas Pelaporan Keuangan Dimoderasi oleh Book-Tax Confirmatory - Kelly Kelly; Androni Susanto (Akuntansi & Ekonomika, 2022)
The purpose of this study is to determine the effect of tax aggressiveness on the financial reporting aggressiveness in Indonesia because both practices are closely related to the profits presented in the financial statements where these financial statements are the center of attention for investors and the general public. In addition, there is a Book-Tax Confirmatory variable as a moderator of the relationship between the two which is allegedly able to create a trade-off and there is also a variable operating cash flow and company size. This study uses a sample of companies on the IDX during 2017-2021 with a purposive sampling method, with the results of tax aggressiveness and book-tax confirmatory having no effect on the financial reporting aggressiveness. However, another result obtained is that operating cash flow has a significant positive effect and company size has a significant negative effect on financial reporting aggressiveness.